The joy of sweat : the strange science of perspiration - Everts, Sarah (W.W. Norton & Company, 2021)
"A taboo-busting romp through the shame, stink, and strange science of sweating. Sweating may be one of our weirdest biological functions, but it's also one of our most vital and least understood. In The Joy of Sweat, Sarah Everts goes behind the taboo and delves into its role in the body-and in human history. She reveals the wondrous mechanics of the sweat glands and the millions of sweat pores in human skin. She explores why sweat is salty, why what you eat can affect the color of your sweat, and why we sweat when stressed (and whether it can be controlled). She takes part in a sweat dating event, traces the controversial history of antiperspirants and deodorants, considers the purported health benefits of saunas, sweat lodges, and hammams, and investigates whether "eyewitnesses" to a crime may someday be replaced by "nose-witnesses" who can pick a suspect's body odor out of a police lineup"--